2013
DOI: 10.1097/ccm.0b013e31828a24e3
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Versus Manual Chest Compressions in Out-of-Hospital Cardiac Arrest

Abstract: The ability to achieve return of spontaneous circulation with mechanical chest compression devices is significantly improved when compared with manual chest compressions. In the case of load-distributing band cardiopulmonary resuscitation, it was superior to manual cardiopulmonary resuscitation as the odds of return of spontaneous circulation were over 1.6 times greater. The robustness of these findings should be tested in large randomized clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 21 publications
0
34
2
Order By: Relevance
“…Because of the inclusion of recent large trials in this review, our conclusions can be firmer than those of the most recent update of the Cochrane review. 7 They also differ from those of another recent review and meta-analysis, 19 which found, mainly from observational evidence, an improvement in the odds of ROSC with mechanical chest compression.…”
Section: Discussionmentioning
confidence: 60%
“…Because of the inclusion of recent large trials in this review, our conclusions can be firmer than those of the most recent update of the Cochrane review. 7 They also differ from those of another recent review and meta-analysis, 19 which found, mainly from observational evidence, an improvement in the odds of ROSC with mechanical chest compression.…”
Section: Discussionmentioning
confidence: 60%
“…Concerning pig models, certain authors have reported that mechanical chest compression, whatever the device, provides better coronary and thus myocardial perfusion and a greater probability of ROSC [22,23]. The same conclusions have been drawn in studies on cerebral perfusion or on cerebral blood low, and perfusion pressures recorded in the internal carotid were greater with mechanical methods than with the manual method [24].…”
Section: Discussionmentioning
confidence: 75%
“…2,3 They also allow for prolonged resuscitation, with documented success after 80 min in one case report. 4 AM-CPR devices have been found to improve coronary and cerebral perfusion pressures [5][6][7] and return of spontaneous circulation in out-of-hospital cardiac arrests, 8 although this has not withstood systematic review. [9][10][11] Complications associated with mechanical CPR devices are often assumed to be similar to those associated with manual CPR, and studies comparing head-to-head complication rates are sparse.…”
Section: Introductionmentioning
confidence: 99%